Effectiveness mapping of open raceway pond and tubular photobioreactors for sustainable production of microalgae biofuel. (September 2016) - Pawar, Sanjay
Abstract: The production of microalgal biofuels seems to be viable on a large scale with the use of wastewater and freely available sunlight for cultivation of microalgae. In this review article, the scale-up and operational aspects have been addressed for mass production of microalgae using wastewater and sunlight in both open raceway pond (ORP) and tubular PBRs, and the outcomes of previous studies are critically reviewed for different cases. Suitable strategies have been proposed for enhancing the productivity considering operational difficulties in various types of PBRs such as ORP, horizontal loop tubular, and vertical tubular column. The importance of mapping of solar intensity and rainfall data is discussed in the context of large scale production. The costs of biodiesel production evaluated by several researchers were found to vary with respect to the followed route/path in their analyzes. These evaluations are compared with respect to the objectives of this study.